Procedure guideline for iodine-131 whole-body scintigraphy for differentiated thyroid cancer (version 3) - Dietlein, M.; Dressler, J.; Eschner, W.; Grünwald, F.; Lassmann, M.; Leisner, B.; Luster, M.; Reiners, C.; Schicha, H.; Schober, O. (Nuklearmedizin - NuclearMedicine, 2007)
Version 3 of the procedure guideline for 131I whole-body scintigraphy (WBS) is the counterpart to the procedure guideline for radioiodine therapy (version 3) and specify the interdisciplinary guideline for thyroid cancer of the Deutsche Krebsgesellschaft concerning the nuclear medicine part. 131I WBS 3–6 months after 131I ablation remains a standard procedure in an endemic area for thyroid nodules and the high frequency of subtotal surgical procedures. Follow-up without 131I WBS is only justified if the following preconditions are fulfilled: low-risk group pT1–2, pN0 M0 with histopathologically confirmed pN0, 131I uptake <2%, 131I WBS during ablation without any suspicious lesion, stimulated thyroglobulin (Tg)-level 3–6 months after ablation <2 ng/mL, and absence of anti-thyroglobulin- antibodies with normal recovery-testing. If patients from the low-risk group show normal 131I WBS 3–6 months after ablation and stimulated Tg is of <2 ng/mL, there will be no need for additional routine 131I WBS. If patients from the high-risk group show normal 131I WBS and stimulated Tg-level of <2 ng/mL 3–6 months after ablation, the follow- up care should include repeated stimulated Tgmeasurements. If the Tg-level remains below 2 ng/mL, an additional 131I WBS will be not necessary. The recommended intervals for stimulated Tg-testing are adapted to the prior intervals for 131I WBS-testing in the high-risk group. Increased anti-thyroglobulin-antibodies or incomplete recovery-testing make an individual strategy of follow- up care necessary, which include 131I WBS.
Keywords: Thyroid cancer; scintigraphy; radioiodine; procedure guideline